Enhancing Students’ Critical Thinking Skills and Motivation Using STEM Project-Based Learning (PjBL-STEM) Through a Simple Hydraulic Jack Project - Hartono, Rudi; Winarno, Nanang; Hernani, Hernani (Jurnal Pendidikan MIPA, 2024)
This study presents an investigation of the use of STEM Project-Based Learning (PjBL-STEM) as a treatment in the experimental class compared to conventional learning in the control class in improving students' critical thinking skills and learning motivation. The focus of the study was Pascal's Law lessons with a special project in the form of developing a simple hydraulic jack. So far, science learning carried out in schools has made students complain, as it is still rote, teacher-centered, unrelated to real-life developments, and rarely integrates technology. This study, therefore, used a quantitative method with a quasi-experimental design involving 60 ninth-grade students in Pasaman Regency who were evenly divided into control and experimental classes using purposive random sampling techniques. Data was collected through a questionnaire on critical thinking skills and learning motivation, after the implementation of PjBL-STEM. The results demonstrated a significant difference between the two groups, with an independent T-test yielding a value of 0.24 for critical thinking skills and 0.33 for learning motivation. The PjBL-STEM model has been proven to improve student's critical thinking skills with an N-Gain of 0.46 (moderate category) and students' learning motivation with an N-Gain of 0.49 (moderate category).      Keywords: critical thinking skills, learning motivation, Pascal's Law, PjBL-STEM. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1976-1999